A Picture of Abanded Children in Padang, A Human Interest Radio Feature - Hadi Permana; Sumira Sumira; Dhini Aulia (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
Abandoned children is  one of the problems faced by Padang city. Many reasons make the number of abanded children  still high. Although, the news about abandoned children have been posted in  newspaper,  magazine even online and   social media,  but  seen that they just inform in partially. Therefore the researchers conducted a project on presenting the data on the picture of abanded children in padang in form of radio feature.  It is expected that this radio feature can give useful information about the reason why they “work on the street”, the life that they run  everyday. Hence it is hope that it can touch the human care of people and government to find the best solution for them. The data  was gotten from the result of interview by using recorder tools. Then Cool Edit Pro 2.1 application was  used to  edit and mix the voice . Moreover this project applied the stages of making radio feature likes pre-production, production and post-production. The result of thisl project were  in form of audio, radio feature  with 15 minutes duration, and the English script with  756 word.